Volume 4: Turbo Expo 2002, Parts a and B 2002
DOI: 10.1115/gt2002-30590
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Analyses of Wet Compression Process in the Compressor of Gas Turbine

Abstract: Thermodynamic model of wet compression process is established in this paper. The topics of ideal wet compression process, actual wet compression process, water droplet evaporative rate, wet compression work, inlet evaporative cooling, concept of wet compression efficiency, aerodynamic breaking of water droplets etc. are investigated and discussed in this paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 0 publications
0
30
0
Order By: Relevance
“…where k is the turbulent kinetic energy, ε is the turbulent kinetic energy dissipation rate and c μ is a model constant. Then, one could possibly evaluate the local Stokes number according to: According to Zheng et al [29], particles smaller than 5 m μ in diameter can follow the flow closely in gas turbines. This is because in their opinion, small particles have small response time, thus achieving velocity equilibrium with the continuous phase in a small amount of time.…”
Section: Stokes Numbermentioning
confidence: 99%
See 1 more Smart Citation
“…where k is the turbulent kinetic energy, ε is the turbulent kinetic energy dissipation rate and c μ is a model constant. Then, one could possibly evaluate the local Stokes number according to: According to Zheng et al [29], particles smaller than 5 m μ in diameter can follow the flow closely in gas turbines. This is because in their opinion, small particles have small response time, thus achieving velocity equilibrium with the continuous phase in a small amount of time.…”
Section: Stokes Numbermentioning
confidence: 99%
“…Since particles smaller than 5-20 m μ in diameter can follow the flow very closely [2], [29], dispersion of particles due to turbulence can be considered negligible. It was also thought that if a small initial particle diameter were chosen then the momentum exchange between phases would be low.…”
Section: Effect Of Water Injection On Rotor Performance Under Design mentioning
confidence: 99%
“…Thermodynamic and analytical studies on wet compression have indicated that it can improve the compressor performance and the overall gas turbine performance [1][2][3][4][5][6]. Thermodynamic models of ideal and actual wet compression processes, developed by Zheng et al [1], clearly showed performance gains achievable with the wet compression. White and Meacock [2] discussed the high fogging effects on the work of compression and the effects on the stage-by-stage compressor performance.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 It takes advantage of the large amount of latent heat of evaporative water to cool the air. Researches showed 1% of water injection increased the gas turbine power up to 10% and thermal efficiency to 3%.…”
Section: Introductionmentioning
confidence: 99%